Detrimental effect of dissolved natural organic matter on molybdenite flotation. (March 2023) - Li, Jialei; Deng, Wen; Liu, Zhicheng; Pei, Bin; Ning, Shuai; Cai, Zi; Liu, Ruizeng
Highlights: Two NOM components (polysaccharides and proteins) can be adsorbed onto molybdenite surfaces. The adsorption of NOM introduces a detrimental effect on molybdenite flotation. The detrimental effect due to BSA was significantly more than that due to SA. Abstract: Dissolved natural organic matter (NOM) is ubiquitous in aquatic environments, and polysaccharides and proteins are two commonly existing components of NOM. In this study, we employed sodium alginate (SA), which is a model polysaccharide, and bovine serum albumin (BSA), which is a model protein, to investigate the effect and mechanism of the two NOM components on molybdenite flotation. The results of the flotation test and contact angle measurement demonstrated that both the two NOM components could result in reductions in the flotation recovery and surface hydrophobicity of molybdenite, and reductions due to BSA were significantly more than those due to SA. The results from the X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy, and microcalorimetry demonstrated that both the two NOM components could be adsorbed onto the molybdenite surfaces. The adsorption of BSA onto the molybdenite surfaces was stronger than that of SA. This study revealed that the two NOM components in process water (polysaccharides and proteins) can introduce a detrimental effect on molybdenite flotation.